Desain Alat Bantu Pemotong Tahu dengan Pendekatan Metode Nigel Cross Dan Value Engineering - Rizqi Wahyudi; Asrori Latif (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2026)
The main issue at Pak Sujadi's tofu factory is the cutting process, which is still done manually and results in size variation defects. The manual tofu cutting process produces 47 defective pieces due to size variation and takes 81.79 seconds. Improving the efficiency of the production process has become the main focus in the development of tools in the food industry, including at Pak Sujadi's tofu factory. This research aims to design a more efficient tofu cutting tool using the Nigel Cross method and value engineering. The Nigel Cross method is applied through seven systematic stages, from goal classification to improvement details (value engineering). The value engineering approach is used to reduce costs without compromising the quality and functionality of the tool. The results of the tofu cutter research show that it can reduce the cutting process time by 70.44% and decrease the defect rate of tofu size variation by 95.74%. The value engineering method reduces the material costs of the tool by 22%. The materials used in the tool consist of grip rubber handle pads, hollow aluminium handles, handle supports, and cutting matrices made of stainless-steel plates.